Zinc isotope fractionation during grain filling of wheat and a comparison of zinc and cadmium isotope ratios in identical soil–plant systems. Issue 1 (26th April 2018) - Wiggenhauser, Matthias; Bigalke, Moritz; Imseng, Martin; Keller, Armin; Archer, Corey; Wilcke, Wolfgang; Frossard, Emmanuel
Summary: Remobilization of zinc (Zn) from shoot to grain contributes significantly to Zn grain concentrations and thereby to food quality. On the other hand, strong accumulation of cadmium (Cd) in grain is detrimental for food quality. Zinc concentrations and isotope ratios were measured in wheat shoots ( Triticum aestivum ) at different growth stages to elucidate Zn pathways and processes in the shoot during grain filling. Zinc mass significantly decreased while heavy Zn isotopes accumulated in straw during grain filling (Δ 66 Znfull maturity–flowering  = 0.21–0.31‰). Three quarters of the Zn mass in the shoot moved to the grains, which were enriched in light Zn isotopes relative to the straw (Δ 66 Zngrain–straw −0.21 to −0.31‰). Light Zn isotopes accumulated in phloem sinks while heavy isotopes were retained in phloem sources likely because of apoplastic retention and compartmentalization. Unlike for Zn, an accumulation of heavy Cd isotopes in grains has previously been shown. The opposing isotope fractionation of Zn and Cd might be caused by distinct affinities of Zn and Cd to oxygen, nitrogen, and sulfur ligands. Thus, combined Zn and Cd isotope analysis provides a novel tool to study biochemical processes that separate these elements in plants.